2003
DOI: 10.5380/ret.v2i2.3473
|View full text |Cite
|
Sign up to set email alerts
|

A Mathematical Model for Direct Evaporative Cooling Air Conditioning System

Abstract: Air conditioning systems are responsible for increasing men's work efficiency as well for his comfort, mainly in the warm periods of the year. Currently, the most used system is the mechanical vapor compression system. However, in many cases, evaporative cooling system can be an economical alternative to replace the conventional system, under several conditions, or as a pre-cooler in the conventional systems. It leads to a reduction in the operational cost, comparing with systems using only mechanical refriger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…The correlation proposed by Dowdy et al [38] as shown in Eq. (24) was obtained from the experiment results of evaporative cooling with the surface covered by a rigid cellulose media saturated with water and was ever used by some researcher correctly [39]. So the present model used the correlation of Eq.…”
Section: Heat and Mass Transfer Modelsmentioning
confidence: 99%
“…The correlation proposed by Dowdy et al [38] as shown in Eq. (24) was obtained from the experiment results of evaporative cooling with the surface covered by a rigid cellulose media saturated with water and was ever used by some researcher correctly [39]. So the present model used the correlation of Eq.…”
Section: Heat and Mass Transfer Modelsmentioning
confidence: 99%
“…Watt (1963) developed the first serious analyses of direct and indirect evaporative systems; Leung (1995) presents an experimental research of the forced convection between an air flow and an inner surface of a horizontal isosceles triangular duct; Halaz (1998) presented a general dimensionless mathematical model to describe all evaporative cooling devices used today; Camargo, Cardoso and Travelho (2000) developed a research where a thermal balance study for direct and indirect cooling systems was developed; Camargo and Ebinuma (2002) presented the principles of operation for direct and indirect evaporative cooling systems and the mathematical development of the equations of thermal exchanges, allowing for the determination of heat transfer convection coefficients for primary and secondary air flow; Dai and Sumathy (2002) investigated a cross-flow direct evaporative cooler, in which the wet honeycomb paper constitutes the packing material and the results indicate that there exists an optimum length of the air channel and the performance can be improved by optimizing some operation parameters; Liao and Chiu (2002) developed a compact wind tunnel to simulate evaporative cooling pad-fan systems and tested two alternative materials; Al-Sulaiman (2002) evaluated the performance of three natural fibers (palm fiber, jute and luffa) to be used as wetted pads in evaporative cooling; Camargo, Ebinuma and Silveira (2003) presents a thermoeconomic analysis method based on the first and second law of thermodynamics and applied to an evaporative cooling system coupled to an adsorption dehumidifier; Hasan and Sirén (2003) investigated the performance of two evaporatively heat exchangers operating under similar conditions of air flow and inlet water temperatures; Camargo, Ebinuma and Cardoso (2003) presents the basic principles of the evaporative cooling processes for human thermal comfort and presents the mathematical development of the thermal exchanges equations, allowing the determination of the effectiveness of saturation. CAMARGO, J. R. Evaporative cooling: water for thermal comfort.…”
Section: Recent Developmentsmentioning
confidence: 99%
“…Watt [1] developed the first serious analyses of direct and indirect evaporative systems; Leung [2] presents an experimental research of the forced convection between an air flow and an inner surface of a horizontal isosceles triangular duct; Halasz [3] presented a general dimensionless mathematical model to describe all evaporative cooling devices used today; Camargo, Cardoso and Travelho [4] developed a research, where a thermal balance study for direct and indirect cooling systems was developed; Camargo and Ebinuma [5] presented the principles of operation for direct and indirect evaporative cooling systems and the mathematical development of the equations of thermal exchanges, allowing for the determination of heat transfer convection co-efficients for primary and secondary air flow; Dai and Sumathy [6] investigated a cross-flow direct evaporative cooler, in which the wet honeycomb paper constitutes the packing material and the results indicate that there exists an optimum length of the air channel and the performance can be improved by optimizing some operation parameters; Liao and Chiu [7] developed a compact wind tunnel to simulate evaporative cooling pad-fan systems and tested two alternative materials; AlSulaiman [8] evaluated the performance of three natural fibers (palm fiber, jute and luffa) to be used as wetted pads in evaporative cooling; Camargo, Ebinuma and Silveira [9] presents a thermoeconomic analysis method based on the first and second law of thermodynamics and applied to an evaporative cooling system coupled to an adsorption dehumidifier; Hasan and Sirén [10] investigated the performance of two evaporatively heat exchangers operating under similar conditions of air flow and inlet water temperatures; Camargo, Ebinuma and Cardoso [11] presents the basic principles of the evaporative cooling processes for human thermal comfort and presents the mathematical development of the thermal exchanges equations, allowing the determination of the effectiveness of saturation.…”
Section: Recent Developmentsmentioning
confidence: 99%